Лесные сказки - Притулина Надежда (Коллекция любимых сказок, 2016)
Экземпляры: ф.13 (20171020) / Инвентарный номер: 54478 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 77 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6